Effectiveness and cost-effectiveness of a guided and unguided internet-based Acceptance and Commitment Therapy for chronic pain: Study protocol for a three-armed randomised controlled trial. - Jiaxi Lin; Marianne Lüking; David Daniel Ebert; Monica Buhrman; Gerhard Andersson; Harald Baumeister (Internet Interventions, 2015)
Background: Acceptance and Commitment Therapy (ACT) is an effective intervention for the treatment of chronic pain. Internet-based pain interventions might be an effective and cost-effective way to overcome treatment barriers of traditional face-to-face pain interventions such as the lack of availability and accessibility. However, little is known about the general (cost-)effectiveness of internet-based pain interventions and the specific (cost-) effectiveness of guided and unguided pain interventions. Therefore, the aim of this study is to investigate the effectiveness and cost-effectiveness of a guided and unguided ACT-based online intervention for persons with chronic pain (ACTonPain). Methods: ACTonPain is a pragmatic three-armed randomised controlled trial comparing ACTonPain with or without therapist guidance against a waitlist control group. Both active conditions differ only with regard to guidance provided by an eCoach, who sends feedback after each module. This study aims to include 300 participants. Randomisation and allocation will be performed using permuted block randomisation with variable block sizes. The intervention contains seven ACT-based modules with interactive exercises, and audio and video clips. Furthermore, the participants have the opportunity to receive daily text messages. Online self-assessments will take place at pre- and post-treatment, as well as at 6 month follow-up. The primary outcome is pain interference. Secondary outcomes include physical and emotional functioning, pain intensity, ACT-related variables as well as health-related quality of life. Moreover, a cost-effectiveness analysis will be conducted from a societal perspective. Demographic and medical variables will be assessed on the basis of self-reports in order to detect potential moderators or mediators of the effects. The data will be analysed on an intention-to-treat basis and also using per-protocol analyses. Discussion: This study will contribute to the evidence base of internet-based pain interventions and provide valuable information about the treatment success and cost-effectiveness regarding the intervention's level of guidance (self-help only vs. guided self-help). If ACTonPain is shown to be effective, investigations in different healthcare settings should follow, to examine possible ways of implementing ACTonPain into existing healthcare systems. The implementation of ACTonPain could help to shorten waiting times, expand access to pain treatment and, potentially, also reduce treatment costs.